Circuitos elétricos modelados por equações diferenciais especiais - Nogueira, Mariana Lopes (Universidade Federal Rural do Semi-Árido, 2018)
Electrical circuits are widely used in the various devices that have access, being its main components resistors, capacitors and inductors. Such elements when associated cause different behaviors in the electric charge that interconnects them and that can be evaluated through the laws of Kirchhoff. Since the most peculiar factor on which such behavior can be analyzed is time. The temporal variation of loads and currents can be evaluated through mathematical modeling and the use of differential equations in order to predict the final behavior of these. The temporal variation of loads and currents can be evaluated through mathematical modeling and the use of differential equations in order to predict the final behavior of these. It is through the identification of Cauchy-Euler and Bessel equations that this work will verify the analytical behavior of the load and electric current for RC, RL and RLC circuits.
Monografia
Keywords: Circuito RC; RC Circuit; Circuito RL; RL Circuit; Circuito RLC; RLC Circuit; Equação de Cauchy-Euler; Equation of Cauchy-Euler; Equações de Bessel; Equations of Bessel; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA